Managing for commitment : developing loyalty in a changing workplace - Goman, Carol Kinsey (Crisp Pub. Menlo ParkUS, 1991)
Examines the changing, more independent work force in the USA, during the final decade of the twentieth century. Suggests strategies and skills which managers need for building trust and maintaining commitment in the workplace, universally. Communication is discussed, and steps toward employee loyalty are provided.